Business ethics and risk management - Jauernig, Johanna; Luetge, Christoph (Ethical economy, studies in economic ethics and philosophy, 2014)
This volume explores various aspects of risk taking. It offers an analysis of financial, entrepreneurial and social risks, as well as a discussion of the ethical implications of empirical findings. The main issues examined in the book are the financial crisis and its implications for business ethics. The book discusses unethical behaviour as a reputational risk (e.g., in the case of Goldman Sachs) and the question is raised as to what extent the financial crisis has changed the banks' entrepreneurial strategy. The book presents an analysis of the reasons leading to the crisis and identifies them as ethical dilemma structures. In addition, it looks at general questions regarding ethical behaviour and risk taking, such as: To what extent does the social embeddedness or abstraction play a role in guaranteeing ethical behaviour? What conclusions can be drawn from institutional or evolutionary perspectives on risk management? Finally, the book discusses further issues that become factors of risk within and between societies, such as work insecurity, corruption or the problem of facilitation payments as a risk in international transactions